RFID aided SINS integrated navigation system for lane applications. (11th May 2020) - Wang, Qi; Yang, Chang-song; Wu, Shaoen
To improve the lane vehicle position accuracy, RFID technology is applied to correct the position of the SINS irregularly with label positioning. The acceleration data of the vehicle in three directions is measured by the accelerometers of the inertial measurement unit; the attitude matrix is updated in real time using the angular velocity of the gyroscope output space, and the acceleration component is transformed into the geographic coordinate system, and the acceleration of the inertial measurement unit. The data is subjected to an integral operation process to obtain a spatial displacement value of the vehicle. The real-time updating algorithm of the attitude matrix and the processing of the inertial measurement unit signal are presented. The quaternion-based algorithm is used to solve the attitude matrix as well as updating the coordinate system of the inertial navigation attitude matrix in real time. The Hilbert-Huang transform is used to filter the acceleration signal to solve the integrator saturation problem caused by the low-frequency component of the acceleration signal. The EMD algorithm based on the continuous root mean square error is applied in rejecting the low-frequency components in the signal. The simulation experiments show that the system can be reliable and high precision.